Proceedings of the 35th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2002.993939
|View full text |Cite
|
Sign up to set email alerts
|

Embedding facilitation in group support systems to manage distributed group behavior

Abstract: This paper addresses the need for automated facilitation to buttress facilitation efforts in managing behavior in the virtual environment. We assert that it is within this environment that we need to concentrate our efforts as the nature of virtual work brings added challenges to successful facilitation.We propose the concept of embedded facilitation in which we implant intelligent agent based behavioral indicators into GSS systems to serve as the "eyes and ears" of the facilitator, and where, based on these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Previous studies have already shown that automating the technical, repeatable processes of facilitation is considered a positive experience for the participants as well as the facilitator (Lopez et al 2002). However, the tasks that have been automated generally represent the more routine, repeatable tasks that do not necessarily impact or indicate behaviours, and do not support means to develop the skills of inexperienced facilitators.…”
Section: Human Facilitation Vs Automated Facilitationmentioning
confidence: 96%
“…Previous studies have already shown that automating the technical, repeatable processes of facilitation is considered a positive experience for the participants as well as the facilitator (Lopez et al 2002). However, the tasks that have been automated generally represent the more routine, repeatable tasks that do not necessarily impact or indicate behaviours, and do not support means to develop the skills of inexperienced facilitators.…”
Section: Human Facilitation Vs Automated Facilitationmentioning
confidence: 96%
“…All the applications developed to support the group facilitation in e-meetings follow the traditional centralized approach where the system explicitly codifies the facilitation knowledge. Examples include software tools that embed knowledge about the collaborative patterns of interaction [10] and workflows [11] for the most frequently used GDPs. These applications basically suffer from the same obstacles met in the traditional AI mainstream such as [12]: 1) the restrictions to codify the human's knowledge into the computing system; 2) the lack of self-development capabilities for this knowledge; 3) the blackbox perspective over a system disconnected from the environment where the relevant knowledge are extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods and means of facilitation of group interactions are suggested in works (Ettington& Camp, 2002;Dongsik&Seunghee, 2002;Lopez et al, 2002;Weinberger et al, 2003). Markham (2012) suggested an approach to specific management of project performance directed towards building collective knowledge through collaboration.…”
Section: Related Researchmentioning
confidence: 99%